The Humanitarian Agenda 2015: Principles, Power, and Perceptions (One Page Summary) - Feinstein International Center (Tufts Archival Research Center, 2005)
Building on earlier Humanitarianism and War Project studies, the Feinstein International Famine Center at Tufts University is embarking on new independently-funded policy research, aimed at equipping the humanitarian enterprise to better address emerging challenges.